Secondary tar components in the catalytic cracking process of biomass tar - LI Yong-ling; WU Zhan-song (工程科学学报, 2015)
Catalytic cracking experiments were carried out on biomass tar in a fixed-bed reactor to study the influence of reaction temperature and catalyst type on the cracking reaction product, secondary tar. The experimental results show that there is an aromatic trend in the secondary tar components, and the types and content of polycyclic aromatic hydrocarbons (PAHs) both increase with the increase of reaction temperature when using the high-alumina brick as an acid catalyst. The rise of reaction temperature can not only improve the deep conversion of biomass tar and reduce the production rate of secondary tar, but also increase the aromatization degree of secondary tar, which is more likely to cause the catalyst deactivation with carbon deposition. When the reaction temperature is 900℃, the secondary tar components are similar with alkaline catalysts (dolomite or limestone), and their types reduce to about 10, which mainly include complex macromolecular hydrocarbon. However, the secondary tar components are still very complex with the high-alumina brick as an acid catalyst, and their types are nearly 30, including not only macromolecular hydrocarbon but also paraffin hydrocarbon and polycyclic aromatic hydrocarbons, in 2-ring, 3-ring and 4-ring.